The relationship between social support and work engagement of rural teachers: a moderated mediation model - Wu, Shengwen; Xu, Qiangqiang; Tian, Huidong; Li, Rongrong; Wu, Xiaopeng (Frontiers in Psychology, 2025)
AimThis paper aims to investigate the relationship between social support and rural teachers’ work engagement while exploring the mediating effect of mindfulness in teaching and the moderating effect of psychological safety.MethodsA sample of 866 rural teachers was recruited, in order to complete the Mindfulness in Teaching Scale, Social Support Rating Scale, Psychological Safety Scale, and Utrecht Work Engagement Scale.ResultsThe study findings indicate that: (1) social support positively influenced the work engagement of rural teachers; (2) further, mindfulness in teaching partially mediated the effect of social support on rural teachers’ work engagement; (3) psychological safety moderated the second half of the pathway of “social support → mindfulness in teaching → work engagement” while the positive correlation between mindfulness in teaching and work engagement was stronger among rural teachers with high psychological safety.ConclusionSocial support documented a strong correlation with work engagement while mindfulness in teaching mediated the pathway between the aforementioned variables. Furthermore, psychological safety moderated the second half of the mediated pathway (the link from mindfulness in teaching to work engagement). Hence, the study outcomes reveal the influential mechanism of social support on the work engagement of rural teachers. This finding suggests that we need to further improve the social support system and its effect mechanism in order to improve the rural teachers’ work engagement. At the same time, it is also very important to create a good psychological working environment to ensure that they maintain a good level of mindfulness in teaching.